Natural Dyes from Plants Extract and Its Applications in Indonesian Textile Small Medium Scale Enterprise - Anastasia Wheni Indraningsih (Eksergi)
Textile industry is an industry that uses dye a lot. Most of the textile industry use synthetic dyes, mainly because it is easy to obtain, guaranteed availability, provide variety of colors and do not easily fading, but in terms of health and safety, waste of textile dyes is very dangerous because it contains heavy metals such as chromium (Cr), tin (Sn), copper (Cu) and zinc (Zn). These metals can be carcinogenic if it accumulates in the human body. On the other hand, the use of natural dyes from plants extracts has many advantages compared to synthetic dyes, such as safe for human’s health and environmental friendly. However there are several drawbacks of natural dyes such as not easily available in the market, not many color choices available and easily fade when compared to synthetic dyes. Therefore, this paper contains review the availability of natural dyes, their extraction and its application in Indonesian textile small scale enterprises.